2015
DOI: 10.1371/journal.pone.0135032
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Carbon Monoxide Protects against the Development of Shock and Mitochondrial Injury following Hemorrhage and Resuscitation

Abstract: AimsCurrently, there is no effective resuscitative adjunct to fluid and blood products to limit tissue injury for traumatic hemorrhagic shock. The objective of this study was to investigate the role of inhaled carbon monoxide (CO) to limit inflammation and tissue injury, and specifically mitochondrial damage, in experimental models of hemorrhage and resuscitation.ResultsInhaled CO (250 ppm for 30 minutes) protected against mortality in severe murine hemorrhagic shock and resuscitation (HS/R) (20% vs. 80%; P<0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Thus, the HO-1 system is thought to constitute an essential cytoprotective component against HSR-induced oxidative organ damage. Although CO is a byproduct of heme breakdown, the molecule itself has been reported to possess anti-inflammatory and anti-apoptotic properties mediated through several signaling pathways, including p38 mitogen-activated protein kinases (MAPK), nuclear factor κB (NF-κB), the nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing-3 (NLRP3)-dependent inflammasome, and modulation of mitochondrial biogenesis, among others (4956). CORMs, which release CO, also have been reported to exert a cytoprotective effect against organ injury through the same signaling pathways as CO (2628,54,57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the HO-1 system is thought to constitute an essential cytoprotective component against HSR-induced oxidative organ damage. Although CO is a byproduct of heme breakdown, the molecule itself has been reported to possess anti-inflammatory and anti-apoptotic properties mediated through several signaling pathways, including p38 mitogen-activated protein kinases (MAPK), nuclear factor κB (NF-κB), the nucleotide-binding domain, leucine-rich-containing family, pyrin domain-containing-3 (NLRP3)-dependent inflammasome, and modulation of mitochondrial biogenesis, among others (4956). CORMs, which release CO, also have been reported to exert a cytoprotective effect against organ injury through the same signaling pathways as CO (2628,54,57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, administration of CORM ameliorates inflammation-related diseases such as sepsis [4, 5] and collagen-induced arthritis [6]. There are many other disorders, such as fibrosis [7], injuries and shock after hemorrhage [8, 9] as well as ischemic lung injuries [10], that were shown to be mitigated by CO. It has also been demonstrated that 10–50 μM CORM-3 mitigates cell death caused by various stresses such as hypoxia/reoxygenation and paraquat administration [1].…”
Section: Introductionmentioning
confidence: 99%
“…Low CO concentrations exert anti-inflammatory and cytoprotective effects (Thiemermann, 2001 ) (Figure 1 ). In line with this, beneficial effects of inhaled CO (100–300 ppm), or CO-releasing donors (e.g., CORMs) have been reported during hemorrhagic shock in both small and large animals (Gomez et al, 2015 ), and/or acute lung injury (ALI) of various origin. The underlying mechanism comprises alterations of cell energy utilization, and preservation of mitochondrial function, e.g., increased anti-oxidative capacity and modulation of reactive oxygen species (ROS) signaling (Lee et al, 2011 ; Gomez et al, 2015 ).…”
Section: Carbon Monoxide (Co)mentioning
confidence: 68%
“…In line with this, beneficial effects of inhaled CO (100–300 ppm), or CO-releasing donors (e.g., CORMs) have been reported during hemorrhagic shock in both small and large animals (Gomez et al, 2015 ), and/or acute lung injury (ALI) of various origin. The underlying mechanism comprises alterations of cell energy utilization, and preservation of mitochondrial function, e.g., increased anti-oxidative capacity and modulation of reactive oxygen species (ROS) signaling (Lee et al, 2011 ; Gomez et al, 2015 ). Briefly, CO-induced ROS signaling exerts cytoprotection and anti-inflammation via mitogen-activated protein kinase (MAPK) (Otterbein et al, 2000 ), regulates vasomotor response in vascular smooth muscle cells but also O 2 sensing by the interaction of CO with Ca 2+ -dependent K + -channels (Riesco-Fagundo et al, 2001 ) and exerts anti-proliferative effects through modulating NADPH oxidase activity (Taille et al, 2005 ) (Figure 2 ).…”
Section: Carbon Monoxide (Co)mentioning
confidence: 68%